A contribution to the Italian validation of the Parenting Interaction with Children: Checklist of Observations Linked to Outcome (PICCOLO) - Montirosso, Rosario; Castagna, Annalisa; Butti, Niccolò; Innocenti, Mark S.; Roggman, Lori A.; Rosa, Elisa (Frontiers in Psychology, 2023)
PICCOLO (Parenting Interactions with Children: Checklist of Observations Linked to Outcomes) is an observational instrument designed to assess four domains of parenting interactions that promote early child development (Affection, Responsiveness, Encouragement, and Teaching). Although PICCOLO has been validated in the United States for children as young as 4 months of age, the current focus is on parents with children aged between 10 and 47 months. This study contributes to the validation of the Italian translation of the PICCOLO by testing its psychometric properties and examining whether factors such as the child’s age and child’s sex are related to the four domains of parenting interactions. To these aims, 152 mothers of children aged 10-47 months from three Italian regions participated in the study. Results indicate that the PICCOLO Italian version has acceptable inter-rater agreement, split-half reliability, and stability over time. Furthermore, the Italian version confirmed the robustness of the factor structure proposed in the original version. While there were no significant differences by child gender on the domains of parenting interactions, the Affection scores decreased with age. Overall, these results demonstrate that the Italian version of the PICCOLO is a reliable measure of maternal interactions with children. The psychometric properties of the instrument make it appropriate for general research purposes and for assessment of parenting before and after support interventions.